Upaya Meningkatkan Kemampuan Berbicara Melalui Metode Bermain Peran Pada Anak Usia 6-8 Tahun Di Sekolah Dasar Aisyah Lubuklinggau - Hartati Ratna Juita (Peneliti.net, 2019)
Speaking is one aspect of language skills and is also a target of language learning for children aged 6-8 years, including preschool children who have characteristics of distinctive physical and psychological development. One of the highlights of children aged 6-8 years is that they are already fond of chatting. Based on the observations of researchers the problem that is often encountered in SD Aisyah Lubuklinggau is the delay in speaking that is saying words that are not perfect, such as the letters R, S, L, Z, Y, F, C in the pronunciation there are still some lisp. Of the 19 students, only 25% or 5 people were able, while 75% or 16 people were categorized as less. So it must be corrected immediately so that in the teaching and learning process there is no communication barrier between the teacher and the child and between children and their peers. For this reason researchers are motivated to improve children's speaking skills by using role playing methods while paying attention to the characteristics of early childhood language development.